Early outcome after intravenous thrombolysis in patients with acute ischemic stroke - Pornpatr A. Dharmasaroja (2018)
Background : Patients with acute ischemic stroke who had early neurological improvement had better functional outcome. The purpose of this study was to determine factors associated with early clinical improvement and early worsening in patients with acute ischemic stroke treated with intravenous thrombolysis. Patients and Methods : Patients treated with intravenous recombinant tissue plasminogen activator (rtPA) between August 2008 and November 2010 were the subjects of this study. Early improvement was defined by marked, clinical improvement or complete recovery at 24 h (National Institutes of Health Stroke Scale (NIHSS) 0-4 at 24 h). Early worsening was defined by an increase in NIHSS ≥1 from baseline. The baseline characteristics were compared between patients with and without outcome of interest. Results : Of the 203 patients studied, 19 (9.4%) patients had complete recovery and 68 (33.5%) patients had marked clinical improvement (NIHSS 1-4) at 24 h. Most patients with early clinical improvement (86%) had favorable outcome at three months. Of the 22 (10.8%) patients who had early clinical worsening, only three (14%) patients achieved favorable outcome at three months and six (29%) patients died. Multivariate analysis revealed that older age (≥70 years old) (odd ratio (OR) 0.498, P=0.049), severe stroke (NIHSS ≥15) (OR 0.154, P < 0.0001) and having intracerebral hemorrhage (ICH) (OR 0.364, P=0.032) were inversely associated with early improvement. History of transient ischemic attack (TIA) (OR 7.724, P=0.043) and ICH (OR 4.477, P=0.008) were related to early worsening. Conclusions : The presence of early clinical improvement or worsening within 24 h after treatment with rtPA had major impact on the outcome at three months.